Rabindra Nath Tagore and Sarojini Naidu: A Comparative Study - Rana, Sunita (International Journal of Psychosocial Rehabilitation, 2020)
Both Tagore and Naidu are illustrious luminaries in the firmament of Indo – English poetry. They made a binding contribution to it and gave it a permanent place in the poetical map of the world. Both Tagore and Naidu rendered incalculable service to Indian literature by interpreting the quintessence of Indian culture to the western world. They evoke in images and rhythms the spectacles of Indian life and artically moulded English language for poetically communicating the typical Indian atmosphere and feelings. Tagore’s lyrics, says W.B.Yeats, are “The work of supreme culture ,they yet appear as much the growth of the common soil as the grass and the rushes A whole people ,a whole civilization immeasurably strange to us, seems to have been taken up into this imagination; and yet we are not moved because of its strangeness, but because we have met our own image, as though we had walked in Rossetti’s willow wood, or heard, perhaps for the first time in literature our voice as in a dream. “ In Sarojini’s poems we find India poetically and picturesquely revealed. She writes about India’s festivals and faiths, the customs and traditions, the flowers and bazaars, the aspects and events of life, the bangle sellers and palanquin bearers, the dancers and fishers.